2011
DOI: 10.1159/000323372
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Surgical and Hardware-Related Complications of Deep Brain Stimulation

Abstract: Objective: To evaluate the incidence of surgical and hardware-associated complications of deep brain stimulation (DBS) for a range of movement disorders. Methods: The study design is a retrospective analysis and review of surgical and hardware complications of DBS performed by a single surgeon from 1999 to 2009. A total of 153 cases of DBS (298 electrodes) for various movement disorders and a minimum follow-up of 1 year have been included. Two patients could not be implanted. A further 54 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 54 publications
5
65
2
1
Order By: Relevance
“…The rate of infection remained consistently very low the last 5-6 years during the study period. Age at the time of surgery was not found to be statistically significant (p = 0.13) when comparing infected and noninfected groups, confirming the more predominant finding in the literature [9,10,12,13,26]. There was a higher number of PD patients with infection, but this was, by far, the largest group which underwent DBS.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The rate of infection remained consistently very low the last 5-6 years during the study period. Age at the time of surgery was not found to be statistically significant (p = 0.13) when comparing infected and noninfected groups, confirming the more predominant finding in the literature [9,10,12,13,26]. There was a higher number of PD patients with infection, but this was, by far, the largest group which underwent DBS.…”
Section: Discussionsupporting
confidence: 61%
“…The rate of infection, especially the 2.01%, compares favorably across published studies. Still, it is difficult to compare percentages directly because different authors use a variety of criteria to define postsurgical DBS infection [7,8,9,10,11,12,13,14,15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although systemic diseases such as diabetes mellitus, smoking, and relative scalp thinness may theoretically lead to an increased risk of infection, no study has identified any of these factors as definitive risk for infections [17,29,33,34,35,36,37,38,39]. In our study, only 1 patient with hardware-related infection had diabetes mellitus, and none had a known immunodeficiency, precluding a statistical analysis for risk factors.…”
Section: Discussionmentioning
confidence: 74%